Pronunciation practice activities : a resource book for teaching English pronunciation - Hewings, Martin (New York : Cambridge University Press, 2004)
A resource book for teachers that presents pronunciation practice activities for a wide range of levels and using a variety of methods; includes an audio CD with material to support the activities.
Includes bibliographical references (p. 242-243) and index.
Professional
Keywords: English language -- Pronunciation by foreign speakers -- Problems, exercises, etc; English language -- Pronunciation -- Problems, exercises, etc; English language -- Pronunciation -- Study and teaching -- Handbooks, manuals, etc; English language -- Study and teaching -- Foreign speakers -- Handbooks, manuals, etc; English as a second language -- Study and teaching -- Handbooks, manuals, etc; English language -- Problems, exercises, etc; English language -- Pronunciation -- Problems, exercises, etc; English language -- Pronunciation -- Study and teaching -- Handbooks, manuals, etc; English language -- Study and teaching -- Handbooks, manuals, etc